Analytics in sport - O'Donoghue, P. (Journal of Human Sport & Exercise, 2017)
Data analytics is become increasingly used in high performance sport as sports governing bodies and elite sports organisations exploit analytics techniques that have been used successfully in medicine, business, criminology and other domains. However, the term "analytics" has also been misused in sports contexts to describe rather routine data analysis processes. The purpose of the current presentation is to discuss the distinction between data analysis and data analytics. Designing a European International soccer tournament is used as an example of data analytics in sport. There are things that data analytics and more routine data analysis have in common. These include the use of multiple data sources, multiple data types, abstraction and a reductive approach to data processing.